Systemic Immune-Inflammation Index (SII) and NeutrophilLymphocyte Ratio (NLR) as a Promising Predictor for Advanced Stage Events during the Follow-Up Period in Hepato-Gastrointestinal Cancer Patients - Zenjaya, Kellyn Trycia; Biutifasari, Verna; Yudadi, Redemptus; Wibowo, Prajogo (http://dharmais.co.id/, 2024)
Background: Tumor microenvironment has shown the role of inflammation in its progressivity. The heterogeneity of prognosis at the same TNM stage makes it difficult to classify patients who are more at risk of developing advanced stages. This study aimed to provide a deeper insight into the potential of cheap inflammation markers based on the Systemic ImmuneInflammation Index (SII) and Neutrophil-Lymphocyte Ratio (NLR) to predict the advanced stage during the follow-up period in patients with hepato-gastrointestinal cancer.Methods: Case-control research was conducted using 120 data of patients with hepatogastrointestinal cancer (Colorectal cancer (CRC), hepatocellular carcinoma (HCC), gastrointestinal stromal tumor (GIST), esophageal adenocarcinoma (EAC), pancreatic ductal adenocarcinoma (PDAC), cholangio carcinoma (CCA)) taken from patient medical records. The patients were divided into case and control groups based on the presence of advanced stage events during the follow-up period that were further classified by the NLR and SII value. The advanced-stage events were analyzed and compared between the two groups using Chi-Square and logistic regression analysis to perceive the predictive value of each ratio. Results: Patients with advanced-stage hepato-gastrointestinal cancer had higher NLR and SII than patients without advanced stage (p 0.001). The group of patients with advanced stages had an average NLR of 18.45 and an SII of 6588.13. The group of patients without advanced stages had an average NLR of 5.12 and SII of 1545.01. The cut-off value was determined using the ROC curve, for NLR was 6.48 (92.5% sensitivity and 71.2% specificity), and for SII was 2264.24 (92.5% sensitivity and 76.2% specificity).Conclusions: NLR and SII are cheap markers and have considerable potential for predicting advanced stage during the follow-up period in patients with hepato-gastrointestinal cancer. SII is more accurate as a predictor than NLR. These tools can be very useful in identifying the high-risk patients among the same TNM stage.